Scene Continuity in Building The Message of The Song in “Jiwa Yang Bersedih” Music Video - Sanjaya, William (VCD, 2024)
A music video is a short film used to accompany a song. "Jiwa Yang Bersedih" is a music video that tells the story of a woman’s struggle with sadness and her vulnerability in seeking happiness. "Jiwa Yang Bersedih" music video has the application of continuity of content, movement, position, and time in each series of images. These continuities help show the message in the story through each scene shown. This research was conducted to discuss the application of continuity in each shot in building the message of the song in "Jiwa Yang Bersedih" music video. The research method used is qualitative. Meanwhile, the approach used is purposive sampling, namely by taking samples as a description of the research material. The theory used for discussion is continuity theory explained by Blain Brown. From the research that has been carried out, it is concluded that there is application of continuity of content, position, and time throughout the scene. Meanwhile, continuity of movement only applies to scenes 1, 4, 5, 10 and 11. On the other hand, discontinuity in content, position, and time occurs in several scenes. These discontinuities disrupt the storyline, causing an acceleration in the character’s actions in a scene. Furthermore, a discontinuity that is not consistent between shots in each scene could mislead the viewers from the original storyline. Meanwhile, continuity shows the storyline about Ghea’s struggle to find happiness through her shadow.